ANALISIS SEMIOTIKA PEMAKNAAN POSTINGAN GAMBAR VAKSIN PADA AKUN INSTAGRAM @NOBODYCORP - Fadeli, Muhammad; Fitriawardhani, Tira; Kurniawan, Hendro (Universitas Panca Marga, 2023)
This study aims to determine the meaning of vaccine image posts on Instagram @nobodycorp. The research method used in this research is qualitative-descriptive using the concept of semiotic theory from Charles Sanders Pierce. The results of this study indicate that in the study there were 8 images of vaccine posters uploaded from the Instagram account @nobodtycorp and from the eight posters the semiotic analysis theory created by Charles Sanders Pierce was combined with icons, indexes and symbols. Of course, after analyzing the eight posters, they are mutually sustainable and have the meaning of voicing about vaccination.